REKONSTRUKSI WEWENANG PENYIDIKAN DALAMPERKARA TINDAK PIDANA KORUPSI (Kajian Kewenangan Polisi dalam Penyidikan Tindak Pidana Korupsi) - Hibnu Nugroho (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
Investigation is a vital phase in the process of revealing material facts as stated in criminal law in Indonesia. Failure in the investigation process will fatally result in the proofing process in the court. Investigation becomes the starting point of criminal law enforcement. In terms of corruption crime investigation in Indonesia, the investigation is conducted by an investigator team consisting of police investigator, court investigator, and Corruption Eradication Commission investigator. The existence of those investigators, at present, is not stable as there are some problems faced by those institutions.